Synthesis, characterization and evaluation of bioactive cyclodextrin derivatives for bimodal applications in drug delivery - Gonçalves, António Ricardo, 1981- (2017)
Tese de doutoramento, Farmácia (Tecnologia Farmacêutica), Universidade de Lisboa, Faculdade de Farmácia, 2014